Pembelajaran Sosial Termediasi dan Aktivisme Media Sosial untuk Pola Hidup Berkelanjutan di Indonesia - Cahyaningtyas, June; Udasmoro, Wening; Sofjan, Dicky (Jurnal Komunikasi, 2021)
The notion of social media activism has often been linked with both event and heroic acts in the public with the aim to transform the society. The problem with this framework is its reliance uponperformance, while lacking of awareness on the mundane aspects of everyday life, where public issues seep into with its own complexity. To fill this gap, the study uses Social Learning Theory as well as Uses and Gratification Theory to understand to what extent social media supports learning for sustainable living. By way of an ethnographic study on online community, the study found that the women under study have utilized the social media strategically to respond to the health issue and environmental problem, especially after the Covid-19 pandemic, through the discourse practice of sustainable living.Keywords: online community, social media activism, social learning, sustainable living.